2017
DOI: 10.1007/s10557-017-6730-5
|View full text |Cite
|
Sign up to set email alerts
|

Triple Antithrombotic Therapy in Atrial Fibrillation Patients Undergoing PCI: a Fading Role

Abstract: Triple antithrombotic therapy (TAT), consisting of aspirin, a P2Y receptor antagonist and oral anticoagulant (OAC) medication has been considered as an 'unavoidable' strategy for a 1-12 months for atrial fibrillation (AF) patients post acute coronary syndrome or percutaneous coronary angioplasty with stenting. However, TAT has rather poorly been adopted in real life practice, mainly because of an accompanying increased bleeding potential and lack of definitive results of randomized clinical trials. Several reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Regarding patients with AF and CAD, it's often challenging to find the optimal balance between the risk for ischemic and hemorrhagic complications in patients requiring both antiplatelet therapy and OAC with a vitamin K antagonist (VKA) or direct oral anticoagulants (DOACs) (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding patients with AF and CAD, it's often challenging to find the optimal balance between the risk for ischemic and hemorrhagic complications in patients requiring both antiplatelet therapy and OAC with a vitamin K antagonist (VKA) or direct oral anticoagulants (DOACs) (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation represents the most common arrhythmia, whose prevalence significantly increases with age ( Wilke et al, 2013 ); its incidence is also rapidly growing outlining a global epidemic with tremendous burden of disability and mortality worldwide ( Chugh et al, 2014 ). The incidence of CAD in patients with AF is very high ( Kralev et al, 2011 ) and it is estimated that up to 7% of patients undergoing PCI for CAD suffer of AF or have another indication for OAC ( Alexopoulos et al, 2017 ). Furthermore, AF represents a frequent complication in patients with acute myocardial infarction (AMI) ( Ibanez et al, 2017 ), contributing to worsening prognosis, whereas advanced age and heart failure constitute the main predictors for the onset of this arrhythmia in AMI patients ( Schmitt et al, 2009 ).…”
Section: Therapeutic Recommendations In Patients With Atrial Fibrillamentioning
confidence: 99%
“…The same investigation group has afterwards published a post hoc analysis to report reduced risk of all-cause mortality or recurrent hospitalization for both rivaroxaban groups compared with standard therapy one ( Gibson et al, 2017 ). It is important to note that, similar to the WOEST, the PIONEER trial was not powered for an efficacy outcome ( Bhatt, 2016 ); furthermore, patients at very high stroke risk were excluded, as well as those with unknown cause anemia, creatinine clearance <30 mL/min, recent history of significant gastrointestinal bleeding ( Alexopoulos et al, 2017 ). Although a fair percentage of ≥65 years aged patients in the trial, (more than 70% of entire population, with ≥75 years aged accounting to more than 33%) ( Gibson et al, 2016 ), all the above mentioned exclusion criteria present in the trials are frequently found in the real world older patients.…”
Section: New Evidences and Different Strategies: Woest Pioneer Af-pcmentioning
confidence: 99%
“…Triple antithrombotic therapy (TAT), consisting of an oral anticoagulant (OAC) plus dual antiplatelet therapy, was until recently the default strategy to reduce atherothrombotic complications; although with the caveat of increased bleeding risk. 1,2 Lately, the role of TAT has been downgraded compared with dual antithrombotic therapy (DAT) with OAC plus a single antiplatelet agent, mainly driven by the reduction of bleeding event rates, without an apparent trade-off in prevention of ischemic events. 3 The latter is supported by recent randomized controlled trials (RCTs) and meta-analyses comparing antithrombotic regimens with novel OACs (NOACs) or vitamin K antagonists (VKAs), which highlight the superiority of DAT versus TAT regarding bleeding complications and recommend the use of NOAC plus a P2Y 12 inhibitor without aspirin, as a favorable option for most AF patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%